2007
DOI: 10.3904/kjim.2007.22.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Objects in Korean Prisoners

Abstract: Background Foreign objects in the gastrointestinal tract are usually the result of accidental swallowing. Yet foreign object ingestion is often seen in prisoners who mainly desire to leave prison. We report here on a series of 33 Korean prisoners with foreign object ingestion and they were treated endoscopically or surgically. Methods We reviewed the medical records of 33 Korean prisoners (52 episodes) who were admitted due to ingestion of foreign objects between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…In a small study of 36 patients, O'Sullivan et al (7) demonstrated that certain subgroups, such as prisoners and those with psychiatric illness, had a higher frequency of foreign body ingestion. Lee et al (12) also reported on the unusual, complex ingestions in a prison population. More recently, Palta et al (13) examined a group of patients from an urban health care setting, with almost all intentional ingestions in 85% of whom had a psychiatric disease.…”
Section: Discussionmentioning
confidence: 97%
“…In a small study of 36 patients, O'Sullivan et al (7) demonstrated that certain subgroups, such as prisoners and those with psychiatric illness, had a higher frequency of foreign body ingestion. Lee et al (12) also reported on the unusual, complex ingestions in a prison population. More recently, Palta et al (13) examined a group of patients from an urban health care setting, with almost all intentional ingestions in 85% of whom had a psychiatric disease.…”
Section: Discussionmentioning
confidence: 97%
“…Another study involving prisoners who ingested foreign body reported an even higher complication rate of 11.5%. [15]…”
Section: Discussionmentioning
confidence: 99%
“…8 While comparing to studies from other countries, mobile phone ingestion is common in our setup. [9][10][11] The prisoners used to vomit these drug packets rather than letting them pass out in the stool. It should be noted that these packets were intentionally made of relatively large size by the packers, so that they can stay in the stomach and can be vomited back.…”
Section: Discussionmentioning
confidence: 99%